Resource extractivism and alternatives: Latin American perspectives on development - Svampa, Maristella Noemí (2012)
Latin America presents a very polarised scenario. Currently, one of the most remarkable patterns is the passage from the Washington Consensus, based on financial valorization, to the Commodity Consensus, based on the large-scale extraction and exportation of natural goods. The article attempts to characterise the current situation and, at the same time, aims at a presentation of different political and intellectual tendencies: liberal neo-developmentalism, progressive neo-developmentalism and post-developmental thinking. The text analyses some links between these perspectives, especially between liberal neo-developmentalism and progressive neo-developmentalism, because both imply a return to the classical understanding of development in the strong sense, that is, associated with a productivist vision and incaccurate industrialist rhetoric. Finally and against his background, it presents some general lines of contemporary post-developmental thinking.